Horizons Community Board Collection: Biosensors - Liu, Zhiyuan; Mehlana, Gift; Chandrasekaran, Arun Richard (Material Horizons, 2021)
Development of sensing technologies has been one of the prime focus of recent research. In this area of research, scientists have developed different types of materials for use in biosensing, analyzed different biological targets and specimens, and combined nanoscale developments into the macroscopic world for real life applications. In this collection, we have compiled a list of articles that discuss these developments in the area of biosensing. We hope it will provide some insight to recent developments in biosensing and adaptability of ongoing lab-based research for real life applications.